Analysis of the Mechanism for the Development of Allergic Skin Inflammation and the Application for Its Treatment: Overview of the Pathophysiology of Atopic Dermatitis - Tadashi Terui (Elsevier, 2009)
Abstract.: It has been recognized that atopic dermatitis (AD) involves allergen-driven Th2 cell polarization. In patients with AD, cytokines induce allergic inflammatory responses and subsequently enhance IgE production. Recent reports revealed that a reduced barrier function as well as altered immunity are fundamental to the development of AD because barrier disruption due to aberrant filaggrin expression is a pathological factor. However, although recent studies have improved our understanding of the pathogenesis of AD, the overall pathophysiology remains elusive. I herein discuss it based on the natural history of AD. Keywords:: atopic dermatitis, nonatopic dermatitis, barrier dysfunction, filaggrin, IgE autoantibody, allergic inflammation